Promoting Regional Strategic Area of Environmental for the Protection of Essential Ecosystem Areas in East Kalimantan - Mohamad Nasir (Faculty of Law, Mulawarman University, 2024)
This article investigates the legal framework of Essential Ecosystem Areas (EEAs) within Indonesian legislation and the regional government's authority to regulate EEAs to preserve and protect the essential ecosystem in its jurisdiction. By employing a normative juridical approach, this research found that the EEA is regulated in sectoral regulations, such as conservation, environmental, forestry, spatial planning, marine, and regional government, which give inconsistencies and legal gaps and can create legal uncertainty. This study also identified that district or city governments could protect and manage EEAs by stipulating an EEA as the strategic area of environmental (KSLH) or protected area through a decree, subsequently incorporating it into the spatial planning of the regency or city. Additionally, the regional government has the authority to provide policies regarding EEAs governance and institutional management, thereby establishing a comprehensive legal framework for the EEAs.